Some Geometric Observations on Heat Kernels of Markov Semigroups with Non-local Generators - Kristian Evans (Trends in Mathematics, 2022)
In this paper we study the possibility to represent the heat kernel associated with a pseudo differential operator with negative definite symbol with the help of a combination of two metrics associated with the symbol. We discuss in great detail two examples and we outline the consequences of this approach.